Hippocampal 5-HT1A Receptor and Spatial Learning and Memory - Glikmann-Johnston, Yifat; Saling, Michael M.; Reutens, David C.; Stout, Julie C. (Frontiers in Pharmacology, 2015)
Spatial cognition is fundamental for survival in the topographically complex environments inhabited by humans and other animals. The hippocampus, which has a central role in spatial cognition, is characterized by high concentration of serotonin (5-hydroxytryptamine; 5-HT) receptor binding sites, particularly of the 1A receptor (5-HT1A) subtype. This review highlights converging evidence for the role of hippocampal 5-HT1A receptors in spatial learning and memory. We consider studies showing that activation or blockade of the 5-HT1A receptors using agonists or antagonists, respectively, lead to changes in spatial learning and memory. For example, pharmacological manipulation to induce 5-HT release, or to block 5-HT uptake, have indicated that increased extracellular 5-HT concentrations maintain or improve memory performance. In contrast, reduced levels of 5-HT have been shown to impair spatial memory. Furthermore, the lack of 5-HT1A receptor subtype in single gene knockout mice is specifically associated with spatial memory impairments. These findings, along with evidence from recent cognitive imaging studies using positron emission tomography (PET) with 5-HT1A receptor ligands, and studies of individual genetic variance in 5-HT1A receptor availability, strongly suggests that 5-HT, mediated by the 5-HT1A receptor subtype, plays a key role in spatial learning and memory.